1991
DOI: 10.1002/jlb.50.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment With P2-Purinergic Receptor Agonists Induces Phenotypic Modulation of the HL-60 and U937 Human Myelogenous Leukemia Cell Lines

Abstract: In previous studies we have demonstrated that extracellular ATP (and UTP), acting through P2-purinergic receptors, can stimulate the inositol phospholipid signaling system in neutrophils and monocytes, as well as in neutrophil/monocyte progenitor cells. In this study we have examined the ability of extracellular nucleotides to modulate the phenotype of myelomonocytic progenitor cells. As model systems, we utilized the established HL-60 promyelocytic and U937 promonocytic human cell lines which were cultured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…At present, the action mechanism by which the [Ca 2ϩ ] i rise induces differentiation of promyelocytes was not yet completely understood. Some studies reported that expression of the proto-oncogene c-myc is dramatically regulated by the transient elevation of [Ca 2ϩ ] i in HL-60 cells (34,47). In those studies the induction of membrane tyrosine kinase activity also accompanied with a significant reduction of c-myc expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the action mechanism by which the [Ca 2ϩ ] i rise induces differentiation of promyelocytes was not yet completely understood. Some studies reported that expression of the proto-oncogene c-myc is dramatically regulated by the transient elevation of [Ca 2ϩ ] i in HL-60 cells (34,47). In those studies the induction of membrane tyrosine kinase activity also accompanied with a significant reduction of c-myc expression.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytic differentiation of HL-60 promyelocytes results in increased expression of formyl peptide receptors that can be readily monitored by observing the increased effectiveness of fMLP in inducing a rise in [Ca 2ϩ ] i (34). The responsiveness of HL-60 cells to fMLP was substantially increased when the cells were induced to differentiate by treatment with 1.25% DMSO, 100 M histamine, or 100 M dibutyryl cAMP (Fig.…”
Section: Negative Modulation Of Histamine-induced Granulocytic Differmentioning
confidence: 99%
“…The need for a better characterization of P2 purinergic receptors in human immune effector cells is stressed by the recent appreciation that the various and often contradictory responses triggered by ATPe, i.e., stimulation of cell proliferation (11) and differentiation (12), activation of the respiratory burst (7), inhibition of phagocytosis (8), and cytotoxicity (3,4), are due to an interaction with different P2 receptor subtypes expressed either by different immune cells or at different stages of maturation. One of the most intriguing effects of ATP, is reversible plasma membrane permeabilization to molecules of < 900 D ( 13,14), a response that is invariably associated with susceptibility to ATPe-mediated cytotoxicity ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, purines are known to induce U937 phenotypic differentiation (Cowen et al, 1991), and to be involved in recruitment of neutrophils and monocytes to the site of injury (Kunapuli and Daniel, 1998). Thus, in addition to their intracellular functions in energy metabolism and nucleic acid synthesis, nucleotides are now recognized to have important roles as extracellular signaling molecules.…”
mentioning
confidence: 99%